Chemical composition of the leaf oil of Saurusus chinenesis (Lour.) Hort. ex Loud. from Thanh Hoa province - Dai, Do Ngoc; Thang, Tran Dinh (Academia Journal of Biology, 2012)
The leaf oil of Saurusus chinenesis (Lour.) Hort. ex Loud. collected from Tho Xuan district, Thanh Hoa province, in Mar 2009 was isolated by steam distillation to give oil yield 0.15% and analyzed by Capillary GC and GC/MS. Thirty components have been identified accounting more than 95.0% of the oil respectively. The major constituents of this oil appeared to be safrol (19.0%), myristicin (13.3%) and g-elemene (10.9%). Less predominant constituents included germacrene D (7.3%), β-elemene (7.3%), β-caryophyllene (6.8%), d-cadinene (4.5%), α-cubebene (2.9), α-copaene (2.6%), α-caryophyllene (2.5%), α-bergamotene (2.2%), α-bisabolene (1.9%), cadina-1,4-diene (1.9%), camphene (1.4%), bicyclogermacrene (1.4%), germacrene B (1.3%) bicycloelemene (1.0%) and β-bisabolene (1.0%). All the other components were in concentration of less than 0.1-0.9%.